2020
DOI: 10.1002/pros.24017
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian berry extract (Myrciaria jaboticaba): A promising therapy to minimize prostatic inflammation and oxidative stress

Abstract: BackgroundBrazilian berry is a fruit popularly known as “Jaboticaba,” rich in bioactive compounds with antioxidant and anti‐inflammatory properties. Senescence and overweight are increasing worldwide and are considered risk factors to prostatic pathogenesis mainly due to oxidative and inflammatory processes induction. Thus, this study aimed to evaluate the effect of two increasing doses of the patented jaboticaba peel extract (PJE) on oxidative‐stress and inflammation in the prostate of aging or high‐fat‐fed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Other functional properties have been described regarding the jaboticaba bioactive compounds that are involved in its protective effect of the prostate, such as its antioxidant and anti-inflammatory capacity [18,29,30]. Their antioxidant mechanism in the prostate involves the modulation of endogenous antioxidant machinery, downregulating the catalase and SOD2 levels and increasing the GPx3 levels [18]. The authors verified that the antioxidant properties further led to the downregulation of NFkB signaling pathway, which is mainly activated by oxygen reactive species [18].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other functional properties have been described regarding the jaboticaba bioactive compounds that are involved in its protective effect of the prostate, such as its antioxidant and anti-inflammatory capacity [18,29,30]. Their antioxidant mechanism in the prostate involves the modulation of endogenous antioxidant machinery, downregulating the catalase and SOD2 levels and increasing the GPx3 levels [18]. The authors verified that the antioxidant properties further led to the downregulation of NFkB signaling pathway, which is mainly activated by oxygen reactive species [18].…”
Section: Introductionmentioning
confidence: 95%
“…Studies have pointed that diet or eating habits are associated with the etiology of prostate disorders [11,[17][18][19]. High adiposity levels have been related to changes in serum levels of different hormones, such as testosterone, estrogen and insulin; which are linked directly or indirectly to the development of prostate cancer [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, merely the high PJE dose ameliorated the toll-like receptor 4 (TLR4), and nuclear factor κB (NF-κB) contents in aging mice, and IL-1β, SOD2, and IL-6 levels in HFD-aging mice. Authors stressed that PJE had a dose-dependent impact on regulating oxidative-stress and inflammation in HFD-fed aging and aging mice prostate [ 90 ].…”
Section: Anti-prostate Cancer Properties Of Anthocyanidins/anthocyaninsmentioning
confidence: 99%
“…Our group demonstrated that jaboticaba peel extract (JPE) was able to prevent hepatic damages and metabolic disorders, particularly, associated with overweight and aging [ 3 ]. In addition to these findings, for the first time, we identified that JPE administration in senile mice also prevented prostate damages caused by aging and high-fat diet consumption, mostly by anti-inflammatory, antioxidant and anti-angiogenic mechanisms and recovery of hormonal balance [ 4 , 5 ]. However, the action mechanisms related to JPE in the prostatic microenvironment and its targets in the cell are still unclear.…”
Section: Introductionmentioning
confidence: 98%